Surface and quantum chemical parameters of nickel oxide nanostructures suited for ultraviolet-assisted cationic dye degradation - G. Rathika; R. Jagadeeswari; T. Sathiyapriya; P. Selvakumar (Kuwait Journal of Science)
Nickel oxide (NiO) nanostructures were synthesized through chemical precipitation and subsequently analyzed using a scanning electron microscopy (SEM) and X-ray diffraction (XRD). Rietveld refinement of XRD data revealed a cubic structure with lattice parameters of a = b = c = 4.173 Å. Fourier transform infrared spectroscopy and energy dispersive X-ray were employed to analyze the functional group and elemental composition of NiO NPs. The ultraviolet diffuse reflectance spectra indicated an optical band gap of 3.08 eV for synthesized NiO nanoparticles. Surface characteristics were evaluated using the Gwyddion open-source application, and parameters including Ra (mean roughness), Rq (mean square roughness), Rsk (surface skewness), and Rku (kurtosis coefficient) were calculated. The chemical properties of NiO were investigated through density functional theory calculations, and the results aligned well with experimental data. Furthermore, a comparative analysis of the photodegradation of methylene blue (MB) and rhodamine B (RhB) in the presence of UV light was examined, and it followed pseudo-first-order rate kinetics with degradation efficiencies of 82.62% (MB) and 71.31% (RhB), respectively. The electric energy per order for the photodegradation process was calculated to be 9.4 × 102 kWh/m3/order (MB) and 11.7 × 102 kWh/m3/order (RhB). Notably, the low electric energy consumption per order indicated a cost advantage for the reactor setup.